Developments in Business Dispute Resolution in the Digital Era - Ade Onny Siagian; Nurhidayati Nurhidayati; Jaka Santosa (International Journal of Social Science and Humanity, 2025)
Current information technology has a major impact on the ability of individuals to access digital spaces and carry out activities easily and efficiently. In this important business world, various problems often arise and increasingly lead to business disputes. The purpose of this study is to provide an in-depth analysis of the urgency of formulating laws to resolve commercial disputes in the digital era, including the introduction of Online Dispute Resolution (ODR) in Indonesia. Digitalization changes law enforcement, thus requiring a comprehensive study of commercial dispute resolution in the digital era. This study was conducted using a normative research methodology using qualitative data and documents, literature, laws and regulations as a form of research interpretation. Selected secondary data were taken from literature, dictionaries, laws and regulations as reference sources. Disputes that lead to business disputes can be resolved through judicial and non-judicial strategies. In the field of litigation, the Supreme Court (MA) and its judicial bodies have played a role in developing legal products, especially e-Court, which allows registered users to access various administrative mechanisms, including online. These objectives have been met. Case registration and online case access. Implementation of legal processes, reimbursement of costs, electronic summons of parties, and implementation of legal processes electronically. If the dispute is not legal in nature, it can be resolved through Alternative Dispute Resolution (ADR).